(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Liver diseases pose significant public health challenges globally, with increasing incidence due to lifestyle factors, viral infections, and metabolic syndromes. Preventive strategies can significantly reduce the burden of liver disease through early detection, lifestyle interventions, and vaccination programs. This article examines key prevention methods, evaluates existing literature, discusses research findings, and provides practical recommendations for individual and public health interventions.